ANALYSIS OF INHIBITORY EFFECT OF TRANSCRIPTIONAL REGULATORY PROTEIN (STY 4289) OF SALMONELLA TYPHI CT18 BY HOMOLOGY MODELLING - Farid, Anila; Saadia Sadiq; Rehana Rasool; Ghazala Rasool; Ajmal Hussain; Muhammad Fawad (Journal of Ayub Medical College Abbottabad, 2023)
Background: Salmonella typhi cause typhoid fever which is life threatening disease. It effects approximately 600,000 people per annum around the world. Food and water are the integral components through which this disease is transmitted and becomes base of typhoid. It spreads widely where cleanliness is very poor. Objective was to analyse three-dimensional structure of transcriptional regulator of Salmonella typhi CT18 by homology modelling to inhibit virulent effect of salmonella typhi. Methods: Bioinformatics tools and programs like comprehensive Microbial resource (CMR). Interproscan, Basic Local Alignment Search tool (BLAST), Modeller 9.10, Procheck and Prosa were used as bioinformatic tools for effective study of protein. Results: Homology modelling is an appropriate and precise method to find three-dimensional transcriptional regulator to stop its virulency. Conclusion: Homology modelling is computational and accurate method to find 3D structure of transcriptional regulator to inhibit its virulence effect of causing disease.